Expressão da proteína Ras em células endoteliais é dependente de S indecam-4. - Cavalheiro, Renan Pelluzzi [UNIFESP] (2009)
Heparan sulfate (HS) plays an important role in cell behavior due to its ability to interact with a variety of molecules modulating growth factors and enzymes. HS participates in cellular signaling, and the activation of downstream pathways is related to the phosphorylation of cytosolic proteins leading to gene regulation. Previous studies show that syndecan-4 (Syn4), a heparan sulfate proteoglycan, modulates cell adhesion and is involved in the regulation of cell cycle. Thus the aim of the present work was to promote Syn4 knock down on endothelial cells using small hairpin RNA (shRNA) in order to gather information on its effect on cell behavior. For comparison, shRNA-Syn4-EC cells were simultaneously investigated with wild type endothelial cells (EC), as well as endothelial cells that overexpress ras oncogene (EJ-ras-EC) and a control that was transfected with the empty plasmideo (mock EC). The different cells were evaluated regarding the expression of Ras protein (Ras), b1-integrin (b1), fibronectin (FN), biglycan (Big), vascular endothelial growth factor (VEGF), von Willebrand factor (vWF), besides the core protein for syndecan-4 (Syn4) by flow cytometry and confocal microscopy. Clones were selected through sqPCR for Syn4 and [35S]-sulfate incorporation into heparan sulfate (HS) and chondroitin sulfate (CS) chains. Regardless of the transfection, the expression of vWF, an endothelial cell marker, was maintained in all cells, confirming their endothelial origin. The expression of syndecan-4 and incorporation of [35S]- sulfate varied among the different clones of shRNA-Syn4-EC up to 80%. The knockdown of Syn4 lead to significant reduction in the expression of Ras, b-1 integrin and FN, when compared to wild type cells as well as EJ-ras-EC. The overexpression of Ras leads to an overexpression of Syn4 and a decrease in VEGF expression and cellular localization of b-1 integrin. Furthermore, shRNASyn4- EC shows weak adhesion to the substrate, indicating that the lack of Syn4 altered cell-cell and cell-matrix interactions. The combined results clearly show that Syn4 plays an important role in cellular biology.